A Well-Done “Meat Culture” Is Best Served Rare(ly): Review of Annie Potts (Ed.), Meat Culture - Freeman, Carrie (Humanimalia, 2021)
Annie Potts, ed., Meat Culture. Human–Animal Studies, vol. 17. Leiden: Brill, 2016. 296 pp. 45 (pb).